Bridging the Gaps: Mutual Trust and Recognition as Tools for Cooperation of Equals - Malachta, Radovan (Unequal Equals? The Status of Member States in an Integrating European Union, 2026)
This chapter assesses the formal equality of Member States of the European Union in situations where they must rely on other Member States and fully accept the other’s sovereign decisions. It primarily focuses on the area of freedom, security and justice, particularly on judicial cooperation in civil and criminal matters, where the need for the recognition and enforcement of judicial and extrajudicial decisions arises. Only a marginal mention has been made of related areas. First, the focus is on developmental trends in the unification of law in this area, that is, judicial cooperation in civil and criminal matters, particularly after the Amsterdam Treaty. Subsequently, based on an analysis of the case law of the Court of Justice of the European Union, relevant EU regulations, and legal scholarship, this chapter defines and synthesises the concept of mutual trust and examines the relationship between mutual trust and mutual recognition. This issue has been discussed separately in civil and criminal matters. On the one hand is a requirement for recognition without special proceedings, and on the other hand are various regulations and framework decisions that lay the grounds for refusing the recognition of a judgment or its non-execution. All these aspects are evaluated against the background of equality or inequality between Member States, which are obliged to cooperate under EU law, even in the absence of fully uniform rules.